The freshwater crab genera Ghatiana Pati & Sharma, Gubernatoriana Bott, and Inglethelphusa Bott (Crustacea: Decapoda: Brachyura: Gecarcinucidae) revisited, with descriptions of a new genus and eleven new species - Pati, S.k.; Thackeray, T. (Zootaxa, 2018)
The taxonomy of three morphologically related and endemic genera of the northern Western Ghats (Ghatiana Pati & Sharma, 2014, Gubernatoriana Bott, 1970, and Inglethelphusa Bott, 1970) is re-assessed to accommodate several new taxa. We describe a new genus, Sahyadriana gen. nov. and its five new species [S. billyarjani sp. nov., S. pachyphallus sp. nov., S. sahyadriensis sp. nov. (type species), S. tenuiphallus sp. nov., and S. woodmasoni sp. nov.]. Additionally, three new species each of Ghatiana (Gh. botti sp. nov., Gh. pulchra sp. nov., and Gh. rathbunae sp. nov.) and Gubernatoriana (Gu. longipes sp. nov., Gu. marleshwarensis sp. nov., and Gu. wallacei sp. nov.) are described. Five species previously in Gubernatoriana are now transferred to Sahyadriana gen. nov., viz. S. alcocki (Pati in Pati, Thackeray & Khaire, 2016) comb. nov., S. pilosipes (Alcock, 1909) comb. nov., S. thackerayi (Pati in Pati, Thackeray & Khaire, 2016) comb. nov., S. triangulus (Pati & Sharma, 2014) comb. nov., and S. waghi (Pati in Pati, Thackeray & Khaire, 2016) comb. nov. Gubernatoriana basalticola Klaus, Fernandez & Yeo, 2014, is transferred to Ghatiana. Inglethelphusa is still proved to be monotypic. Consequently, Ghatiana now contains eight species, three of which are new; Gubernatoriana, four species, including three new species; Inglethelphusa, one species; and Sahyadriana gen. nov., ten species, including five new species. Sahyadriana pilosipes is rediscovered more than a century after its description. All these genera can be separated from other Indian gecarcinucid crabs by the absence of a flagellum on the exopod of the third maxilliped and a very short G2. The relevant identification keys are revised. Currently, 120 species of freshwater crabs under 35 genera and two families are found in India. Kerala is the most species-rich (35 species) state in India followed by Maharashtra (29 species) and Assam (21 species). The Western Ghats of India now includes 17 genera and 58 species of gecarcinucid crabs. A checklist and distribution of Indian freshwater crabs is provided.